Modern Java EE fundamentals : a back-to-basics approach across APIs and ecosystems (O'Reilly, 2015)
"Java EE technology master Reza Rahman has worked with Java Enterprise Edition since its inception in the mid-90s. In this video, he shares his commanding knowledge of the platform with this review of the primary APIs that make up Java EE7. He explains each API in detail, using demonstrations and a discussion of each API's unique value proposition. APIs covered include JSF, CDI, EJB 3, JPA, Bean Validation, JMS, JAX-RS, WebSocket, and Batch."--Resource description page.